Utilization of Augmented Reality Media in Listening Learning for Explanatory Texts in Junior High Schools - I Putu Krisna Wiryasuta; I Wayan Rasna; Ida Ayu Made Darmayanti (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Problems in learning to listen to explanatory texts in junior high schools are identified as the lack of variety in media used, resulting in low student motivation and a limited understanding of the material. The use of learning media, particularly in listening to explanatory texts, still requires further study to determine its effectiveness. This study aims to analyze the use of Augmented Reality (AR)-based learning media in teaching explanatory texts, with a focus on enhancing the listening skills of ninth-grade students. This qualitative descriptive study, employing a case study design, involved 32 students and one teacher as research subjects. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed descriptively qualitatively using the stages of data reduction, data presentation, and verification of findings. The study's results showed that the average score of student responses to AR media was 87.4, falling within the positive category, indicating that the use of AR media significantly increased student motivation, interest, and engagement in learning to listen to explanatory texts. In conclusion, AR media effectively bridges the gap between conventional learning methods and digital learning needs, and supports the implementation of the Independent Curriculum. The implications of this research provide direction for educators to implement innovative technology-based learning media, thereby optimizing the quality and relevance of 21st-century learning.